Influence of Depression and Anxiety on Satisfaction and Expectation Fulfillment in Foot and Ankle Surgery. Issue 4 (16th October 2019) - Henry, Jensen K.; Roney, Andrew; Hummel, Amelia; Cody, Elizabeth; Ellis, Scott
Category: Ankle, Ankle Arthritis, Arthroscopy, Bunion, Hindfoot, Midfoot/Forefoot, Sports, Trauma Introduction/Purpose: Depression and anxiety are increasingly recognized to have a dramatic impact on patients with musculoskeletal pathologies. They complicate treatment due to complex relationships between pain, function, and affective symptoms. Depression/anxiety can cause social isolation, attention towards painful symptoms, and avoidance of physical exertion, all which may affect patient outcomes in orthopaedic surgery. Prior work has demonstrated that patients with depression/anxiety have greater preoperative expectations of foot/ankle surgery. However, no study to date has investigated the effect depression/anxiety on fulfillment of expectations and patient satisfaction postoperatively. We hypothesized that patients with preoperative depression or anxiety symptoms would have lower rates of expectation fulfillment than patients without affective disorders, particularly for expectations of pain relief and going back to normal. Methods: Patients undergoing elective foot/ankle surgery at a single center were prospectively enrolled. Demographics, diagnoses, and preoperative Foot and Ankle Outcomes Scores (FAOS) were collected. Preoperatively, patients completed an expectations survey, which asks about anticipated improvement in items including pain control, ambulation, function, and more generalized items like going back to normal and preventing foot/ankle pathology from worsening. Depression and anxiety were assessed using the Patient Health Questionnaire (PHQ-8) and Generalized Anxiety Disorder screener (GAD-7) respectively; for both surveys, scores of 10 or more were used to designate depression and anxiety. Patients repeated the expectations survey 2 years postoperatively, answering how much improvement was actually attained for each item. Patients also reported satisfaction with surgery, perception of overall improvement, extent to which expectations were fulfilled, and answered the Delighted- Terrible scale. Survey responses were compared between patients with depression and/or anxiety (D/A) and no D/A patients using t-tests and Chi-square analyses (p<0.05). Results: Of 271 total patients, 53 (20%) met criteria for D/A. D/A and no D/A patients were statistically similar in age (54.4 vs 55.7 yrs), gender (62% vs 66% female), comorbidities, education, ethnicity, and diagnoses. D/A patients had significantly worse preoperative FAOS scores and greater preoperative expectations. Postoperatively, both groups had similar proportions of expectations fulfilled (p=0.292) and improvements in FAOS scores (p>0.225). D/A patients had significantly less expectation fulfillment for ambulation tolerance (77% vs 90%, p=0.017), improving confidence in foot/ankle (77% vs 88%, p=0.049), and going back to normal (76% vs 87%, p=0.043). D/A patients were significantly more dissatisfied (21% vs 9%, p=0.013), had less perceived improvement, and were less likely to want to repeat surgery (p=0.019) or recommend surgery to someone else (p=0.017). Conclusion: D/A patients had significantly lower postoperative rates of overall perceived improvement and satisfaction with surgery compared to patients without affective symptoms. A majority of D/A patients did not meet their expectations for ambulation tolerance, confidence, and returning to normal. However, despite having worse baseline outcomes scores and more preoperative expectations, patients with depression/anxiety had similar improvements in FAOS and proportions of expectations fulfilled postoperatively. Therefore, despite perceived poor outcomes, D/A patients have similar improvements in outcomes and expectation fulfillment. These findings may improve surgeon/patient communication and management of expectations.